Mitochondrial bioenergy alterations in avian HD11 macrophages infected with infectious bronchitis virus - da Silva, Sergio E. L.; Ferreira, Helena L.; Garcia, Andrea F.; Silva, Felipe E. S. [UNESP]; Gameiro, Roberto [UNESP]; Fabri, Carolina U. F. [UNESP]; Vieira, Dielson S. [UNESP]; Cardoso, Tereza C. [UNESP] (Springer Nature, 2018)
To establish an association between mitochondrial dysfunction and apoptosis following infectious bronchitis virus (IBV) infection, HD11 avian macrophage cells were infected with the Massachusetts 41 (M41) strain. Our results show that the M41 strain of IBV induced cytopathic effects followed by the release of new viral particles. Elevated numbers of apoptotic cells were observed at 24, 48 and 72 h post-infection (p.i.). Viral infection was associated with mitochondrial membrane depolarization and reactive oxygen species (ROS) production at all of the examined timepoints p.i. In summary, IBV M41 replication in infected HD11 macrophages seems to induce mitochondrial bioenergy failure, acting as a respiratory chain uncoupler, without compromising viral replication.